A vulnerability index for COVID-19: spatial analysis at the subnational level in Kenya - Macharia, PM; Joseph, NK; Okiro, EA (BMJ Publishing Group, 2020)
Background Response to the coronavirus disease 2019 (COVID-19) pandemic calls for precision public health reflecting our improved understanding of who is the most vulnerable and their geographical location. We created three vulnerability indices to identify areas and people who require greater support while elucidating health inequities to inform emergency response in Kenya.